Comparison of clinical and imaging findings in cats with single and mixed lungworm infection. Issue 6 (June 2019) - Febo, Elettra; Crisi, Paolo Emidio; Traversa, Donato; Luciani, Alessia; Di Tommaso, Morena; Pantaleo, Stefania; Santori, Domenico; Di Cesare, Angela; Boari, Andrea; Terragni, Rossella; Vignoli, Massimo
Objectives: This study has compared clinical and imaging features in 52 cats naturally infected by respiratory nematodes Aelurostrongylus abstrusus, Troglostrongylus brevior and Capillaria aerophila, and in both monospecific and mixed infections. Methods: Medical records of cats with a lungworm disease were retrospectively reviewed. Cats with clinical examination findings, haematobiochemical analysis and thoracic radiography were included in the study and clinical and radiographic scores were assigned. For eight cats CT of the thorax was also available and analysed. A statistical analysis was performed to investigate the potential correlation between clinical and radiographic score, and to evaluate the effect of age, sex and infection on clinical and radiographic severity. Results: Monospecific infections by A abstrusus (32/52), T brevior (6/52) and C aerophila (5/52) and coinfections by T brevior / A abstrusus (7/52), T brevior / C aerophila (1/52) and A abstrusus / C aerophila (1/52) were diagnosed. Cats with mixed infections showed higher clinical scores compared with cats with monospecific parasitoses ( P <0.05), while no differences were observed for radiographic scores. No correlation between clinical and radiographic scores was found (rs = 0.50), and these scores were not affected by patient age or sex. CT, performed on cats infected with A abstrusus, T brevior or A abstrusus/T brevior, provided additional information in cats with mild radiographic signs. Conclusions and relevance: This study indicates that clinical parameters may be more severe in mixed infections than in monospecific parasitoses. A significant correlation between clinical and radiographic score was not detected, while several subclinically infected cats showed radiographic changes. In cats with mild-to-moderate lung patterns, the ventrodorsal/dorsoventral projection showed lesions that are not visible in the lateral projections, especially in the caudal lobes.